2011
DOI: 10.1039/c1cc11063b
|View full text |Cite
|
Sign up to set email alerts
|

Stereocontrol in proline-catalyzed asymmetric amination: a comparative assessment of the role of enamine carboxylic acid and enamine carboxylate

Abstract: The transition state models in two mechanistically distinct pathways, involving (i) an enamine carboxylic acid (path-A, 4) and (ii) an enamine carboxylate (path-B, 8), in the proline-catalyzed asymmetric α-amination have been examined using DFT methods. The path-A predicts the correct product stereochemistry under base-free conditions while path-B accounts for reversal of configuration in the presence of a base.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 21 publications
3
31
0
Order By: Relevance
“…Owing to the high enamine amounts detected in DMSO and MeCN, the first proline-derived Z enamines were detected in solution. The experimental detection of enaminocarboxylate-DBU + ion pairs in DMSO, accompanied by the reduction of the amount of oxazolidinone intermediates below the NMR detection limit support the recently raised explanation of steric shielding for the reversal of enantioselectivity of proline-catalyzed reactions upon the addition of basic amine additives [10,14] as has been proposed for bulky diA C H T U N G T R E N N U N G aryl-A C H T U N G T R E N N U N G prolinol ether catalysts. Moreover, the observed deA C H T U N G T R E N N U N G proA C H T U N G T R E N N U N G ton-A C H T U N G T R E N N U N G ation of the carboxyl group of proline enamines was shown to have an impact on the electron density and, hence, on the nucleophilicity of the enamine moiety, which might be one aspect to explain their increased reactivity, as observed in a previous study by Mayr.…”
Section: Resultsmentioning
confidence: 62%
See 3 more Smart Citations
“…Owing to the high enamine amounts detected in DMSO and MeCN, the first proline-derived Z enamines were detected in solution. The experimental detection of enaminocarboxylate-DBU + ion pairs in DMSO, accompanied by the reduction of the amount of oxazolidinone intermediates below the NMR detection limit support the recently raised explanation of steric shielding for the reversal of enantioselectivity of proline-catalyzed reactions upon the addition of basic amine additives [10,14] as has been proposed for bulky diA C H T U N G T R E N N U N G aryl-A C H T U N G T R E N N U N G prolinol ether catalysts. Moreover, the observed deA C H T U N G T R E N N U N G proA C H T U N G T R E N N U N G ton-A C H T U N G T R E N N U N G ation of the carboxyl group of proline enamines was shown to have an impact on the electron density and, hence, on the nucleophilicity of the enamine moiety, which might be one aspect to explain their increased reactivity, as observed in a previous study by Mayr.…”
Section: Resultsmentioning
confidence: 62%
“…[12] This idea was recently exploited by Mayr and co-workers for the kinetic proof of neighboring-group participation in proline enaminocarboxylate catalysis in acetonitrile and THF, [13] and by Blackmond, Armstrong, and co-workers for the reversal of enantioselectivity in proline-catalyzed a-amination of aldehydes in dichloromethane. [10] At first glance, the stabilization of proline enamines by deprotonation seems to conflict with the rationale of proline enamine stabilization by the stabilized carboxyl proton in solvents with strong hydrogenbond-acceptor performance. [11] However, as postulated for an explanation of the reversal of enantioselectivity with a proline/DBU combination relative to proline, [10] this seeming contradiction may be solved by the assumption of ion pairs between the enaminocarboxylate and the protonated base and the accompanied stabilization of the former carboxyl proton in a salt bridge.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Although various organocatalysts have been developed to reach high level of efficiencies and to widen the scope of substrates, proline, owing to its good performance in a broad range of asymmetric transformations such as aldol [4], Mannich [5], and amination reactions [6] etc., has been identified as a universal catalyst and is still the hot topic in the field of organocatalysis [1][2][3][4][5][6][7][8][9][10][11][12]. For the enamine-mediated process in proline catalysis, the widely accepted Houk-List transition state model (TSA in Scheme 1), which underlines that the proton of the enamine carboxylic acid (intermediate I in Scheme 2) plays an essential role in directing the electrophile approaching the above face of s-trans-enamine in the stereocontrolling addition step, has been successfully employed to rationalize the stereoselectivity of various reactions [2,[13][14][15][16][17][18][19][20][21][22][23][24][25]. Recently, several experimental evidences have shown that the reactivity and selectivity of the proline-catalyzed transformations are sensitive to the basic additives [7][8][9]11,12].…”
Section: Introductionmentioning
confidence: 99%